2009
DOI: 10.1002/cphc.200900004
|View full text |Cite
|
Sign up to set email alerts
|

The Excited‐State Lifetimes in a G⋅C DNA Duplex are Nearly Independent of Helix Conformation and Base‐Pairing Motif

Abstract: DNA photophysics: Femtosecond transient absorption experiments reveal that excited states produced by UV light in a duplex DNA oligonucleotide decay at essentially the same rate in B and Z helix conformers (see figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 44 publications
4
31
0
Order By: Relevance
“…We judge that the reproducibility of successive signals recorded for the same solution is a better criterion than changes in the absorbance of the sample (Fig. SI-2), used in transient absorption measurements of similar systems [8] . nm, before (blue) and after (green) irradiation with 267 nm laser pulses having an intensity 0.5 GW/cm 2 .…”
Section: Experimental Setups and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We judge that the reproducibility of successive signals recorded for the same solution is a better criterion than changes in the absorbance of the sample (Fig. SI-2), used in transient absorption measurements of similar systems [8] . nm, before (blue) and after (green) irradiation with 267 nm laser pulses having an intensity 0.5 GW/cm 2 .…”
Section: Experimental Setups and Methodsmentioning
confidence: 99%
“…The detailed nature of these states is still under debate [1][2][3][4][5][6] . However, based on results from transient absorption measurements performed for short helices at selected wavelengths, the following picture has been proposed [6][7][8] . The initially populated * states relax within 100 fs to energetically low-lying excimers or exciplexes decaying with time constants up to ca.…”
mentioning
confidence: 99%
“…The Quinn group [350] reported that the nonradiative decay takes longer for the Z-form than for the B-form of poly (dCdG)·poly(dGdC), with experimental monoexponential time constants of 16-20 ps. By contrast, the Kohler group [351] reported that the experimentally observed nonradiative decay lifetime of (dCdG) 9 ·(dGdC) 9 is independent of the helix conformation (also in the region of several picoseconds). These findings call for theoretical studies on Z-DNA to check whether the established theoretical explanations for B-DNA photodynamics carry over to the more loosely stacked Z-DNA strands.…”
Section: Other Helical Conformations and Modified Strandsmentioning
confidence: 91%
“…AT base pairing measurably affects nonradiative decay rates in AT duplexes, but other experiments have shown that excimer lifetimes are insensitive to base-pairing motif and helix conformation [184]. de La Harpe et al studied a d(GC) 9 · d(GC) 9 duplex by fs-TA spectroscopy [184].…”
Section: Long-lived Excited States and Helix Conformationmentioning
confidence: 98%
“…de La Harpe et al studied a d(GC) 9 · d(GC) 9 duplex by fs-TA spectroscopy [184]. This self-complementary DNA duplex adopts different conformations in solution depending on the ionic strength and pH, allowing the effect of different base stacking motifs on excited-state dynamics to be studied in a system of constant base sequence.…”
Section: Long-lived Excited States and Helix Conformationmentioning
confidence: 98%